2018
DOI: 10.1111/cea.13279
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary approach to the management of adult eosinophilic oesophagitis in the United Kingdom

Abstract: Dietary intervention is effective for the management of eosinophilic oesophagitis (EoE) in both adults and children. 1 The majority of research has been conducted in Spain or the United States, 1 with no studies of dietary intervention published in the United Kingdom. Restrictive elimination diets can be challenging and swallowed topical corticosteroids have also been shown to be an effective treatment in adults. 2 Despite their efficacy, disadvantages include risk of candidiasis, 3 potential long-term effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…A single centre UK study that included a dedicated dietitian reported high levels of efficacy with elimination diets in a retrospective service evaluation. 138 This approach is supported by the American Academy of Allergy, Asthma and Immunology recommendation that ‘a referral to a registered dietitian for any individual prescribed an elimination diet for EoE’. 139 Therefore, support from an experienced dietitian is recommended to mitigate these risks as well as to help the patient to succeed on the diet.…”
Section: Managementmentioning
confidence: 99%
“…A single centre UK study that included a dedicated dietitian reported high levels of efficacy with elimination diets in a retrospective service evaluation. 138 This approach is supported by the American Academy of Allergy, Asthma and Immunology recommendation that ‘a referral to a registered dietitian for any individual prescribed an elimination diet for EoE’. 139 Therefore, support from an experienced dietitian is recommended to mitigate these risks as well as to help the patient to succeed on the diet.…”
Section: Managementmentioning
confidence: 99%
“…The variety of specialists consulted by a large number of patients in the CCAD database attests to the attempt to diagnose and manage these conditions by a multidisciplinary team (MDT). In fact, recent literature promotes the management of EGIDs by an MDT, which includes a specialized dietician [ 39 - 41 ]. Diagnosis of EoE was mostly done at the gastroenterology clinic, without further information about sign and symptom presentation.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first presentation of the rationale for the MDT in eosinophilia ( Supplementary Tables 1, 2 ; Table 1 and Figures 2 – 4 ). The MDT function is a well-established tool across medical disciplines ( 172 177 ), and MDTs have been implemented in departments treating eosinophilic esophagitis, possibly improving patient outcomes ( 180 , 181 ), and have also been considered in Loeffler’s endocarditis ( 182 ). However, one difference between the MDT for patients with eosinophilia and other scheduled MDTs is that the MDT for eosinophilia typically starts by challenging and discussing the working diagnosis ( Figure 5 ), whereas the diagnosis has been established unquestionably in (almost all referred patients) MDTs.…”
Section: Discussionmentioning
confidence: 99%